The Relationship Of Body Mass Index To Some Health-Related Physical Fitness Components For Students Aged (16-17) Years (Journal of the College of Basic Education, 2025)
The research aimed to examine the relationship between body mass index (BMI) selected health-related physical fitness components among preparatory stage male students aged (16–17) years in the Mutafawkeen High School for Boys in Erbil Governorate. The researcher used the descriptive research for its suitability to the nature of the research problem. The research sample consisted of (36) students from the Mutafawkeen High secondary School for boys. Mass and Height measurements were used to determine the body mass index (BMI). Health-related physical fitness components were measured by tests (cardiorespiratory fitness test (1200) meters run/walk (10-18 years), sitting from lying with bent knees and hands on the chest, forward trunk bend from sitting position (flexibility box), jumping from standing). The results showed a relationship between BMI, flexibility, and cardiorespiratory fitness, as well as a relationship between some health-related fitness variables (flexibility test with cardiorespiratory fitness test, abdominal muscle endurance, and jumping from a standing position) and between (muscle endurance with abdominal test and jumping from a standing position). The results showed that the arithmetic mean of BMI reached (25.77 kg/m2), which is within the normal limits of the World Health Organization index, with a decrease in the level of health-related physical fitness in the research sample compared to global levels, as the arithmetic mean of the cardiorespiratory fitness test (1200 meters run/walk) reached (3.27 minutes), and the sit-up test with bent knees (25.25 times/minute). , the flexibility box test (1.73 cm), and the jump test from a standstill (1.73 m). The researcher recommended the necessity of increasing the physical education portion in middle schools, while emphasizing the need to conduct physiological measurements regarding the body mass index (BMI) and health-related physical fitness components for school students on a regular basis.